DAMPAK STIGMA SOSIAL TERHADAP REHABILITASI NARAPIDANA PEREMPUAN DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Witdodo, Sucipto (Ensiklopedia of Journal, 2024)
This study examines the impact of social stigma on the rehabilitation of female inmates in correctional facilities. Female inmates often face significant challenges due to societal perceptions that label them as unworthy or dangerous, which adversely affects their rehabilitation process. Utilizing a qualitative research approach, data were collected through interviews with female inmates and correctional staff. The findings reveal that social stigma not only hampers the emotional well-being of female inmates but also limits their access to rehabilitation programs and support. The study concludes that addressing social stigma is essential for improving rehabilitation outcomes and facilitating successful reintegration into society.Keywords: social stigma; female inmates; rehabilitation; correctional facilities; reintegration.